2022
DOI: 10.3389/fphys.2022.920675
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of estrogen receptor beta classical genomic activity enhances systemic and adipose-specific response to chronic beta-3 adrenergic receptor (β3AR) stimulation

Abstract: White adipose tissue (WAT) dysfunction independently predicts cardiometabolic disease, yet there is a lack of effective adipocyte-targeting therapeutics. B3AR agonists enhance adipocyte mitochondrial function and hold potential in this regard. Based on enhanced sensitivity to B3AR-mediated browning in estrogen receptor (ER)alpha-null mice, we hypothesized that ERβ may enhance the WAT response to the B3AR ligand, CL316,243 (CL).Methods: Male and female wild-type (WT) and ERβ DNA binding domain knock-out (ERβDBD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 103 publications
0
3
0
Order By: Relevance
“…The resulting mitochondrial pellet is resuspended in 150 μL of mitochondrial phosphate buffer (MiPO3). Mitochondria were given 30 min on ice prior to being loaded in the Oroboros for assessment of mitochondrial respiration using high-resolution respirometry (Oroboros Oxygraph-2 k, Oroboros Instruments, Innsbruck, Austria) ( Cunningham et al, 2021 , 2022 ; Queathem et al, 2022 ). The mitochondrial respiration protocol following addition of mitochondria to the Oroboros consisted of malate (2 mM) and glutamate (5 mM) for state 2 respiration (measuring complex I leak with substrate rate limiting), ADP (1,000 μM) for state 3 – Complex I (measuring oxidative phosphorylation through complex I), succinate (10 mM) for state 3 – complex I + II (measuring oxidative phosphorylation capacity through both complex I and II), FCCP (0.25 μM) for uncoupled (maximal oxygen consumption), and Cyto C (5 μM) to verify quality of mitochondrial preparations.…”
Section: Methodsmentioning
confidence: 99%
“…The resulting mitochondrial pellet is resuspended in 150 μL of mitochondrial phosphate buffer (MiPO3). Mitochondria were given 30 min on ice prior to being loaded in the Oroboros for assessment of mitochondrial respiration using high-resolution respirometry (Oroboros Oxygraph-2 k, Oroboros Instruments, Innsbruck, Austria) ( Cunningham et al, 2021 , 2022 ; Queathem et al, 2022 ). The mitochondrial respiration protocol following addition of mitochondria to the Oroboros consisted of malate (2 mM) and glutamate (5 mM) for state 2 respiration (measuring complex I leak with substrate rate limiting), ADP (1,000 μM) for state 3 – Complex I (measuring oxidative phosphorylation through complex I), succinate (10 mM) for state 3 – complex I + II (measuring oxidative phosphorylation capacity through both complex I and II), FCCP (0.25 μM) for uncoupled (maximal oxygen consumption), and Cyto C (5 μM) to verify quality of mitochondrial preparations.…”
Section: Methodsmentioning
confidence: 99%
“…However, in the study by Porter et al described previously, the protein content of both ERα and ERβ was highly correlated with the mitochondrial protein uncoupling protein 1 (UCP-1) across sexes and ages [ 126 ]. Those same authors, using preclinical models, have demonstrated that both exercise and a selective beta 3 adrenergic receptor ligand, CL316,243, increased the density of ERβ in both subcutaneous and visceral fat, suggesting that stimulation of adipocyte metabolism may cause increased ERβ expression on adipocytes [ 128 , 129 ]. Meanwhile, a series of preclinical studies in rodents have shown that selective activation of ERβ has metabolism-boosting effects [ 108 , 109 , 130 ].…”
Section: Exercise Improves Metabolic Health Following the Menopausementioning
confidence: 99%
“…Bridging this back to whether changes in ER expression may affect exercise responsiveness after the menopause, a preclinical rodent study revealed that ERβ-mutated mice were resistant to the adipose-tissue-specific metabolic adaptations with exercise that were observed in wild-type mice [ 132 ]. Intriguingly, both exercise [ 133 ] and the adipose-tissue-specific “exercise mimetic” CL316,243 [ 53 , 129 , 134 ] increase ERβ density selectively in adipose tissue. Capitalizing on this enhanced ERβ expression, particularly following hormone loss, combining selective ERβ activation with exercise (or drugs that affect adipose tissue metabolism) may be an effective strategy to maximize maintenance of metabolic health following the menopause.…”
Section: Exercise Improves Metabolic Health Following the Menopausementioning
confidence: 99%